Comment on 'rigorous benchmarking of T cell receptor repertoire profiling methods for cancer RNA sequencing' - Davydov, Alexey N; Bolotin, Dmitry A; Poslavsky, Stanislav V; Chudakov, Dmitry M (Briefings in bioinformatics, 2023)
Transcriptome sequencing has become common in cancer research, resulting in the generation of a substantial volume of RNA sequencing (RNA-Seq) data. The ability to extract immune repertoires from these data is crucial for obtaining information on infiltrating T- and B-lymphocyte clones when dedicated amplicon T-cell/B-cell receptors sequencing (TCR-Seq/BCR-Seq) methods are unavailable. In response to this demand, several dedicated computational methods have been developed, including MiXCR, TRUST and ImRep. In the recent publication in Briefings in Bioinformatics, Peng et al. have conducted an intensive, systematic comparison of the three previously mentioned tools. Although their effort is commendable, we do have a few constructive critiques regarding technical elements of their analysis.
Keywords: cancer immunology; receptory antigenů T-buněk; sekvenční analýza RNA; Benchmarking; T-cell receptor; B-Lymphocytes; benchmarking; nádory; B-lymfocyty; Receptors, Antigen, T-Cell; Sequence Analysis, RNA; immunogenomics; lidé; computational methods; Neoplasms; RNA sequencing; TCR sequencing; Humans